Courses and Exercises for Algebra 01 - Saadaoui, Kheir (Mohamed Boudiaf University of M'sila, 2024)
This document contains lessons and exercises for the first year of university mathematics in the Algebra 1 course. The topics covered are in accordance with the ministerial program in English. It has been approved by the scientific committee as a reference for this level after being reviewed by an expert.
Lecture Notes for Algebra 01
Keywords: Logical concepts; Sets and Fonctions; Binary relations on a set; Algebraic structures; Polynomial rings